IDeAS: automated design tool for hetero-chiral protein folds. (14th August 2018) - Ranbhor, Ranjit; Kumar, Anil; Tendulkar, Abhijit; Patel, Kirti; Ramakrishnan, Vibin; Durani, Susheel
Abstract: Incorporating D amino acids in the protein design alphabet can in principle multiply the design space by many orders of magnitude. All native proteins are polymers composed of L chiral amino acids. Practically limitless in diversity over amino acid sequences, protein structure is limited in folds and thus shapes, principally due to the poly L stereochemistry of their backbone. To diversify shapes, we introduced both L- and D α -amino acids as design alphabets to explore the possibility of generating novel folds, varied in chemical as well as stereo-chemical sequence. Now, to have stereochemically-defined proteins tuned chemically, we present the I nverse De sign and A utomation S oftware, IDeAS. Retro-fitting side chains on a backbone with L and D stereochemistry, the software demonstrate functional fits over stereo-chemically diverse folds in a range of applications of interest in protein design.